Mediation of organizational commitment the effect of personality traits and teamwork competencies on organizational citizenship behavior - Fitri Wulandari; Fariqoh Zumrotul Mila (Enrichment : Journal of Management, 2023)
This study purposes to analyze the role of personality traits and teamwork competencies on organizational citizenship behavior (OCB) by mediating organizational commitment to employees of PT. Investama Komando Security. Analyzing what factors influence extra role behavior is very urgent for organizations because it has an impact on organizational performance in the long term. Using qantitative research methods, data was collected using a questionnaire. The analytical tool used in this study was multiple regression with IBM SPSS Version 23 software. This study applied a purposive sampling technique, 124 employees of PT. Investama Komando Security. The results of this study indicate that personality traits have no significant effect on OCB, but have a significant effect on organizational commitment. Teamwork competencies have a significant effect on OCB and also have a significant effect on organizational commitment. Organizational commitment influences OCB. The result of mediating organizational commitment on the influence of personality traits on OCB is full mediation. Mediation of organizational commitment on the effect of teamwork competencies on OCB is partial mediation. The effect of teamwork competencies on organizational commitment indicates the biggest influence. The findings of this study provide a conceptual framework regarding the factors that influence organizational citizenship behavior. The best strategy in increasing Organizational citizenship behavior is to increase the role of teamwork competencies and organizational commitment.